(untitled) (Iter, 2022)
In the present work we will try to elucidate the union between the nature represented in this case by pastors who perform their ordinary tasks relating to problems that were crucial in the Roman world, such as the expropriation of property, love for a slave, economic power , arbitration as a way to solve conflicts, the divinization of Emperor Augustus. For this we will devote ourselves to the study of one of the most beautiful compositions of antiquity, the Bucólicas de Virgilio. It is precisely in the pen of this genius of Latin letters that we can find vulgar man in his natural environment by deciding on these crucial issues the Roman citizen. Before introducing ourselves to the analysis of the eclogues in question we will know a little about the poet and his environment, how much of his personal problems and experiences influenced his verses, without asking too much since we would escape from the proposed objective.